Why do we need a real gender policy in the EU? - Canário, M. (Europe as a Global Actor 2018, 2018)
Gender equality is the fifth Global Goal for Sustainable Development created by the United Nations and it also constitutes a crucial point in the European Union agenda, bearing in mind that equal pay is included in the 1957 Treaty of Rome as one of its founding principles. Over the last 60 years, issues related to women's rights have been eclipsed by economic and financial issues within the European Union. Despite the current commitment to gender equality in policymaking remains uncertain, the year of 2017 was a friend to women lobbying especially inside the EU. But there is still a clear paradox, given that the reality concerning women’s rights and opportunities within the EU is not exemplary regarding EU’s discrepancy between its rhetoric and its action. Gender mainstreaming is not an effective policy for the promotion and acceleration of gender equality and ends up not having the desired effect: to integrate a gender perspective into all stages of EU programs. This paper presents a number of issues related to the need for and urgency of a gender policy within the EU: is gender mainstreaming viable? How can we use civil society organizations to demand a real gender policy? What is the impact of having a concrete policy on gender equality for EU Member States? Can the EU be a global actor in terms of gender equality?